Benchmark of the extension of frozen-density embedding theory to nonvariational correlated methods: the embedded-MP2 case - Sen, Reena; Gonzalez-Espinoza, Cristina E.; Zech, Alexander; Dreuw, Andreas; Wesolowski, Tomasz A. (Journal of chemical theory and computation, 2021)
The extension of the frozen-density embedding theory for nonvariational methods [J. Chem. Theory Comput. 2020, 16, 6880] was utilized to evaluate intermolecular interaction energies for complexes in the Zhao-Truhlar basis set. In the applied method (FDET-MP2-FATLDA), the same auxiliary system is used to evaluate the correlation energy by means of the second-order Moller-Plesset perturbation theory (MP2), as in our previous work [J. Chem. Phys. 2019, 150, 121101]. Local density approximation is used for E-xcT(nad)[rho(A), rho(B)] in both cases. Additionally, the contribution to the energy due to the neglected correlation potential was evaluated and analyzed. The domain of applicability of the local density approximation for E-xcT(nad)[rho(A), rho(B)] was determined based on deviations from the interaction energies from the conventional MP2 calculations. The local density approximation for E-xcT(nad)[rho(A), rho(B)] performs well for hydrogen- or dipole-bound complexes. The relative errors in the interaction energy lie within 330%. While for charge-transfer complexes, this approximation fails consistently, and for other types of complexes, the performance of this approximation is not systematic. The sources of error are discussed in detail.
Gesehen am 16.08.2021